Depression and suicidal ideation in hemodialysis patients (Annals of Medical Research, 2022)
Aim: Depression and suicide are more common comorbidities in end-stage renal disease patients than in healthy populations, but suicide has rarely been studied. Our research aimed to evaluate the relation between depressive mood and suicidal ideation in hemodialysis cases.Materials and Methods: 112 hemodialysis patients were included in the study. The sociodemographic characteristics of the patients and the laboratory test results were obtained from the file records. Beck Depression Inventory (BDI) and Suicidal Ideation Scale (SIS) were administered through face-to-face interviews.Results: We enrolled 112 volunteer hemodialysis patients [female/male, 48/64; age 59.9±13.5 years; hemodialysis duration 36.5 months (6-291)]. We divided the cases into two groups based on their BDI scores as those with depressive mood (BDI score ≥ 17, n= 47) (42%) and those without (BDI score < 17, n= 65) (58%).  Of the cases with depression, 38 (68.1%) were female, and 15 were male (31.9%)( p
Keywords: Depression; suicidal ideation; hemodialysis